The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.2139/ssrn.2623489
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Quality of Growth: A Note

Abstract: The transition from Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs) has substantially shifted the policy debate from growth to inclusive growth. In this short note, we revisit the trust-growth nexus by exploiting a dataset on quality of growth (QG), recently made available to the scientific community. The empirical evidence is based on interactive contemporary and non-contemporary quantile regressions. Inequality and human development modifying variables are used as additional contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 17 publications
0
38
0
1
Order By: Relevance
“…In essence, with QR, parameter estimates are derived at multiple points of the conditional distributions of quality of growth (Koenker & Bassett, 1978). The QR estimation strategy is increasingly being employed in development literature, inter alia in: health (Asongu, 2014), corruption (Billger & Goel, 2009;Okada & Samreth, 2012) and quality of growth (Asongu & Rangan, 2015) studies. Therefore, the techinque enables us to examine the effects of social spending (health and education) on quality of growth with particular emphasis on best-and worst-performing developing countries in terms of growth quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, with QR, parameter estimates are derived at multiple points of the conditional distributions of quality of growth (Koenker & Bassett, 1978). The QR estimation strategy is increasingly being employed in development literature, inter alia in: health (Asongu, 2014), corruption (Billger & Goel, 2009;Okada & Samreth, 2012) and quality of growth (Asongu & Rangan, 2015) studies. Therefore, the techinque enables us to examine the effects of social spending (health and education) on quality of growth with particular emphasis on best-and worst-performing developing countries in terms of growth quality.…”
Section: Methodsmentioning
confidence: 99%
“…In the transition from Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs), the policy debate has been shifting from growth to growth quality. The relevance of the underlying policy debate has been fuelled by the April 15 th 2015 publication of World Development Indicators which revealed that poverty has been decreasing in all regions of the world, with the exception of Sub-Saharan Africa (Asongu & Kodila-Tedika, 2015;Caulderwood, 2015;World Bank, 2015) in spite of (i) over two decades of growth resurgence that began in the mid-1990s (Fosu, 2015) and (ii) the sub-region hosting seven of the ten fastest growing economies in the world (Asongu & Rangan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Issues of immiserizing growth are clearly apparent in the second point because SSA has been enjoying over two decades of growth resurgence (Fosu, 2015, p. 44) on the one hand, and on the other hand, the sub-region is host to seven of the ten fastest growing economies in the world (Asongu & Rangan, 2016). Hence, the World Bank's position that about 45% of countries in the sub-region are substantially off-track from attaining the Millennium Development Goals (MDGs) extreme poverty target clearly shows that accounting for regional and other specificities documented by Mlachila et al (2014) is relevant for results with more targeted policy implications.…”
Section: Liberalisation Of Information and Communication Technologiesmentioning
confidence: 99%
“…The independent variables of interest or mobile money service indicators from Mosheni-Cheraghlou (2013) In accordance with recent inclusive literature, the control variables entail: education spending, government stability, credit, inflation, foreign direct investment (FDI) and remittances (Anand et al, 2013;Asongu & Rangan, 2016;Odhiambo, 2009Odhiambo, , 2011Odhiambo, , 2010bOdhiambo, , 2013Asongu & Nwachukwu, 2016). A complete definition of the variables is disclosed in Appendix 1.…”
Section: Datamentioning
confidence: 99%
“…First, the April 2015 World Bank report has revealed that poverty has been decreasing in all regions of the world with the exception of Africa where 45% of countries in sub-Saharan Africa (SSA) are substantially off-track from achieving the MDGs poverty target (Asongu and Kodila-Tedika, 2015). Second, the continent has enjoyed over two decades of growth resurgence (Fosu, 2015) and is currently host to seven of the ten fastest growing economies of the world (Asongu and Rangan, 2015). Third, one of the most important challenges the continent would be confronted with in the post-2015 development agenda is energy crisis (Akinyemi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%